Factors Associated with The Incidence of Undernutrition in Children Under Five Years of Age in The Working Area of The Fatukanutu Health Center Kupang Regency - Sori Duda, Nartiani Rambu; Ruliati, Luh Putu; Limbu, Ribka (Universitas Nusa Cendana, 2024)
Malnutrition is one of the health problems in Indonesia. Malnutrition in children under five will increase morbidity and mortality. This study aims to determine factors related to the incidence of malnutrition in children under five related to maternal knowledge about nutrition, parenting patterns, education, family socio-economic condition, and infectious diseases in the work area of Fatukanutu Health Center, Kupang Regency. The study was an analytical survey with a cross-sectional study design. The sample consisted of 55 mothers who had undernourished children and were selected randomly. Data were collected by using questionnaires. The chi-square test was used in this study to assess the correlation between each variable and malnutrition. Nutritional knowledge (p=0.000), maternal parenting patterns (p=0.032), education level (p=0.000), occupation (p=0.002), infectious diseases (p=0.002), and family income (p=0.046) were related to nutritional status. Maternal nutritional knowledge needs to be improved through community-based education to support mothers in choosing and processing nutritious food for toddlers. Economic improvement by village government is a potential solution to increasing family income.